Peran PR Analyst dalam Pengelolaan Media Internal Kompas Gramedia - Rafiq, Almira Felia; Claretta, Dyva (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2023)
AbstractPublic Relations handles few important roles to manage communication medium for its public, one of them by using digital PR which is website. PR Analyst Kompas Gramedia through a portal MyKG.id trying to presenting various informations and news related to the company itself for internal publics. This study is aims to analyze about how PR Analyst Kompas Gramedia implementate the PR roles in managing informations through MyKG.id, based on four Public Relations roles by Dozier and Broom which are Communcation Facilitator, Communication Tehnician, Expert Prescriber, and Problem Solving Facilitator. This type of study is qualitative descriptive. The result of this study are PR Analyst managing the whole news by doing real coverages and compiling lots of press release from cross-sectors, take advantages of continuous interactive medium such as WhatsApp Group Blast, Email Blast, KGTV, sound building, Instagram account @mykg.id, TikTok account @KompasGramedia, becoming a journalist inresidence, synergized with other division and Kompas Gramedia's publics, manages socialization and education program for the employees of Kompas Gramedia, also presenting solutions and inovations to improve MyKG.id. Keywords: Public Relations, Public Relations Roles, Internal Website of Corporation, Digital PR Abstraksi Public Relations memainkan peran penting dalam pengelolaan saluran informasi kepada publik, salah satunya dengan pemanfaatan digital PR yaitu website. PR Analyst Kompas Gramedia melalui portal MyKG.id menghadirkan ragam berita terkait perusahaan untuk publik internal. Penelitian ini bertujuan untuk menganalisa bagaimana peran yang dijalankan PR Analyst Kompas Gramedia dalam mengelola informasi Website MyKG.id, ditinjau dari empat peran public relations oleh Dozier dan Broom yakni Communication Facilitator, Communication Technician, Expert Prescriber, dan Problem Solving Facilitator. Jenis penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa PR Analyst mengelola berita dengan liputan langsung dan menghimpun berita dari lintas sektor, memanfaatkan media interaktif lanjutan seperti WhatsApp Group Blast, Email Blast, KGTV, Sound Building, Instagram @mykg.id, dan TikTok @KompasGramedia, berperan menjadi journalist inresidence, bersinergi antardivisi dan dengan karyawan Kompas Gramedia, mengadakan kegiatan sosialisasi dan edukasi untuk karyawan Kompas Gramedia, serta menghadirkan solusi dan inovasi untuk perkembangan website MyKG.id.Kata Kunci: Public Relations, Peran Public Relations, Website Internal Perusahaan, Digital PR